2008
DOI: 10.1128/mcb.01465-07
|View full text |Cite
|
Sign up to set email alerts
|

Sphingosine Kinases and Sphingosine-1-Phosphate Are Critical for Transforming Growth Factor β-Induced Extracellular Signal-Regulated Kinase 1 and 2 Activation and Promotion of Migration and Invasion of Esophageal Cancer Cells

Abstract: Transforming growth factor ␤ (TGF␤) plays a dual role in oncogenesis, acting as both a tumor suppressor and a tumor promoter. These disparate processes of suppression and promotion are mediated primarily by Smad and non-Smad signaling, respectively. A central issue in understanding the role of TGF␤ in the progression of epithelial cancers is the elucidation of the mechanisms underlying activation of non-Smad signaling cascades. Because the potent lipid mediator sphingosine-1-phosphate (S1P) has been shown to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
65
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(69 citation statements)
references
References 52 publications
4
65
0
Order By: Relevance
“…We confirmed that Lith-O-Asp treatment decreased a-2,6-and a-2,3-sialylation of integrin-(1; decreased p-FAK(Y31), p-paxillin(Y397), MMP2, MMP9 protein expression; and decreased Rho activity ( (Table 1). For example, CCT6A, which is a chaperonin and stimulates TGF-b-mediated migration and invasion through maturation of sphingosine kinases 1 (34), and WDR1, which is essential for actin dynamics through interaction with cofilin (35), showed decreased expression after Lith-O-Asp treatment. Interestingly, we observed an increase in p-cofilin (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…We confirmed that Lith-O-Asp treatment decreased a-2,6-and a-2,3-sialylation of integrin-(1; decreased p-FAK(Y31), p-paxillin(Y397), MMP2, MMP9 protein expression; and decreased Rho activity ( (Table 1). For example, CCT6A, which is a chaperonin and stimulates TGF-b-mediated migration and invasion through maturation of sphingosine kinases 1 (34), and WDR1, which is essential for actin dynamics through interaction with cofilin (35), showed decreased expression after Lith-O-Asp treatment. Interestingly, we observed an increase in p-cofilin (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that S1P/S1PR1 signaling is indispensable for TGF-␤ signaling in EMT. 33 Thus, it would be interesting to investigate the effect of TGF-␤ signaling in S1PR1-deficient embryos in future.…”
Section: Requirements Of Smad2/3for Vascular Stability 5325mentioning
confidence: 99%
“…45 Moreover, transforming growth factor-␤-induced migration and invasion of esophageal cancer cells was shown to involve SK-1-generated S1P via S1P2 signaling. 46 It should be noted, however, that disruption of the S1P2 gene led to the development of diffuse large B-cell lymphoma (DLBCL) in approximately half of S1P2 Ϫ/Ϫ KO mice within 1.5 to 2 years of age. 47 Thus, long-term targeting of S1P2 might have some unwanted consequences.…”
mentioning
confidence: 99%